Polymers with hydro-responsive topography identiﬁed using high throughput AFM of an acrylate microarray - Hook, Andrew L.; Yang, Jing; Chen, Xinyong; Roberts, Clive J.; Mei, Ying; Anderson, Daniel G.; Langer, Robert; Alexander, Morgan R.; Davies, Martyn C. (Royal Society of Chemistry, 2011)
Atomic force microscopy has been applied to an acrylate polymer microarray to achieve a full topographic characterisation. This process discovered a small number of hydro-responsive materials created from monomers with disparate hydrophilicities that show reversibility between pitted and protruding nanoscale topographies.